Use of Instructional Videos to Augment the Teaching of ICT Practical Sessions in the midst of Higher Students Enrollment (British Journal of Multidisciplinary and Advanced Studies, 2023)
The current study looked at how instructional videos were created and used to augment the practical teaching and learning of information and communication technology (ICT) course. With a sample size of 1620 students, the researcher created customized short instructional videos on the different topics on the course outline and shared videos on the platform of the students in the Fall of 2021/2022 school year. The researcher found evidence that the use of the instructional videos was helpful in the practical lessons. Second, participants indicated that using the instructional videos was their first time in this university. Finally, the participants expressed their desire to use the instructional videos in the near future as well as recommend to their peers in other programmes. Implications for practice are discussed.